RELATIONSHIP USEFULNESS, PERCEIVED EASE OF USE TO REPURCHASE INTENTION E-MONEY: DOES TRUST MATTER? (AT MANAGEMENT STUDENTS IN PRIVATE UNIVERSITAS) - Liliana Dewi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The cashless lifestyle has been growing in the New Normal Era. The increasing public interest in technology has led to product innovations in the electronic field such as electronic money. This study aims to determine the effect of perceived benefits, perceived convenience, and trust on interest in using e-money. This study uses a quantitative method by distributing online questionnaires to 197 e-money users of the 2017 batch of regular class management students of Universitas Ciputra, Surabaya, at least using e-money 3 times. The data were processed with SPSS 21. The result was that perceived benefits and ease of use have a significant effect on intentions to use e-money. Trust has no significant effect on the intention to use e-money. E-money is a necessity without looking at trust as a priority.